Reflections on macroeconomic policy and European unemployment after Maastricht: some evidence - Αλεξίου Κωνσταντίνος (SPOUDAI Journal of Economics and Business, 2003)
Effective economic policies that promote conditions for full employment have yet to be seen. In Europe economic policy has suffered many setbacks and restrictions, due, in the main, to the criteria imposed by the Maastricht treaty. In this paper the policy ramifications, as well as the impact that the Maastricht provisions have exerted on European unemployment, are explored. To this effect empirical evidence suggests that the prevailing 'austere' economic conditions might have contributed to a mediocre economic performance and poor record of employment creation JEL Classification: E12